ADOPSI DALAM HUKUM ISLAM DAN HUKUM INDONESIA - Sainul, Sainul (STAIN Jurai Siwo Metro, 2015)
AbstractThis essay reveal about the procedure of adoption (adoption) in accordance with Islamic law and the legal status of adopted children in force in Indonesia. In Law No. 23 of 2002 on Child Protection determined that the removal of the child should not be decided in religion and blood relationship with the adoptive childs biological parents. Setting Government Regulation No. 54 Year 2007 on the Implementation of Child Adoption namely that the procedures for adoption between Indonesian citizen that a child can lift a maximum of 2 (two) times the distance of at least 2 (two) years. For the validity of the appointment of a child in Indonesia, after a request for adoption through the procedures of the rules in the legislation that exists, adoptions subsequently passed through the last step, namely the presence of a court decision issued by the court in the form of a court warrant or known by the judgment declaratory, that statement from judges that the adopted child is legitimate as a foster child of the adoptive parents who apply for adoption. Court decisions also covers the legal status of the adopted child in the family. The concept of appointment of a child in Islamic law does not recognize adoption of children in the sense of being a child of the absolute, being that there are only allowed or susruhan to maintain with the aim of treating the child in terms of love of giving a living, education or services in all the needs that are not treated as biological children ( nasab). In the Islamic concept, the appointment of a child should not be cut off nasab between the child with his biological parents is based on the Quran Surat Al-Ahzab verse 4,5,37, and 40. This was later associated with the legal consequences arising is about marriage and inheritance system. In marriage a priority nasab guardian for girls is his own father. In inheritance, adopted children does not include the heirs and vice versa, which amount is 1/3 (one third) part of the legacy.Â Keywords: Adoption, children, inheritance, court, marriageÂ AbstrakTulisan ini mengungkap tentang prosedur pengangkatan anak (adopsi) menurut hukum Islam dan status hukum anak angkat yang berlaku di Indonesia. Dalam Undang Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak ditentukan bahwa pengangkatan anak tersebut harus seagama dan tidak memutuskan hubungan darah anak angkat dengan orang tua kandungnya. Pengaturan Peraturan Pemerintah Nomor 54 Tahun 2007 tentang Pelaksanaan Pengangkatan Anak yaitu bahwa tata cara pengangkatan anak antar Warga Negara Indonesia bahwa seorang dapat mengangkat anak paling banyak 2 (dua) kali dengan jarak waktu paling singkat 2(dua) tahun. Untuk sahnya pengangkatan anak di Indonesia, setelah permohonan pengangkatan anak melalui prosedur dari aturan dalam perundang-undangan yang ada, pengangkatan anak selanjutnya disahkan melalui langkah terakhir yaitu dengan adanya putusan pengadilan yang dikeluarkan oleh pengadilan dengan bentuk penetapan pengadilan atau dikenal dengan putusan deklarator, yaitu pernyataan dari Majelis hakim bahwa anak angkat tersebut adalah sah sebagai anak angkat dari orang tua angkat yang mengajukan permohonan pengangkatan anak. Putusan pengadilan juga mencakup mengenai status hukum dari anak angkat dalam keluarga. Konsep pengangakatan anak dalam hukum Islam tidak mengenal pengangkatan anak dalam arti menjadi anak kandung secara mutlak, sedang yang ada hanya diperbolehkan atau susruhan untuk memelihara dengan tujuan memperlakukan anak dalam segi kecintaan pemberian nafkah, pendidikan atau pelayanan dalam segala kebutuhan yang bukan memperlakukan sebagai anak kandung (nasab). Dalam konsep Islam, pengangkatan seorang anak tidak boleh memutus nasab antara si anak dengan orang tua kandungnya berdasarkan Alquran Surat Al-Ahzab ayat 4,5,37, dan 40. Hal ini kelak berkaitan dengan akibat hukum yang ditimbulkan yaitu mengenai perkawinan dan system waris. Dalam perkawinan yang menjadi prioritas wali nasab bagi anak perempuan adalah ayah kandungnya sendiri. Dalam waris, anak angkat tidak termasuk ahli waris begitu juga sebaliknya, yang besarnya adalah 1/3 ( sepertiga ) bagian dari harta peninggalan.Â Kata kunci : Adopsi, anak, waris, pengadilan, perkawinan